Ovarian endometrioid borderline tumor arising from an endometriotic cyst - Hussin, Huzlinda; Abd Ghani, Fauzah (Scopemed Publishing, 2017)
Endometrioid borderline tumor of the ovary is defined as a solid or cystic tumor composed of crowded glands lined by atypical endometrioid type cells and lacking destructive stromal invasion and/or confluent glandular growth. In the literature, it was reported to comprise 2-19% of endometrioid tumors and 2-10% of all borderline tumors. The prognosis for ovarian endometrioid borderline tumor is excellent including that with features of intraepithelial carcinoma or microinvasion. Recurrences and metastases are extremely rare. A 34 years old Chinese lady presented with vaginal bleeding for many months. Intraoperatively, an intact right ovarian tumor measuring 55×10×10 mm was found. Cut sectioned showed a unilocular cyst with hemorrhagic fluid content and a solid tan nodule of 15 mm in diameter was found within the wall. Microscopically, the cystic ovarian tumor showed features of the endometriotic cyst and the solid nodule arising from the cyst wall showed an adenofibromatous pattern of an endometrioid borderline tumor. She also presented with disseminated endometriosis in the omentum and pelvic peritoneum. This kind of case was rarely reported for clinical reference especially on the macroscopic and microscopic features.